Functional outcome of Unstable Distal Radial Fracture Management by External Fixator using the Principle of Ligamentotaxis (Journal of Dhaka National Medical College & Hospital, 2022)
Objective: The aim of the present study was to asscess the functional outcome of Unstable Distal Radial Fracture managed by External Fixator using the Principle of Ligamentotaxis.Methods: A prospective observational study was conducted from July 2016 to June 2018 among 32 patients attending at Orthopaedics and Traumatology department of the Dhaka Medical College Hospital after obtaining requisite consent from the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to asscess the functional outcome of Unstable Distal Radial Fracture managed by External Fixator using the Principle of Ligamentotaxis. The study was approved by the institutional ethical committee.Results: 32 patients were enrolled for the study. The mean age of the patients was 37.56±11.82. More than half of the respondents were male (68.75%). Results were assessed by Demerit point system of Gartland and Werley for functional outcome In this study satisfactory result was seen in 84.37% and unsatisfactory result was seen in 15.63%. All fractures (100%) were united nicely.Conclusion: Unstable distal radial fracture management by external fixator using the principle of ligamentotaxis is an effective method of treatment.J.  Dhaka National Med. Coll. Hos. 2022; 28 (01): 16-19